Neil Gaiman’s Use of Antiquity in Television Series: American Gods and Calliope - Elżbieta Olechowska; Marta Pszczolińska (Clotho)
American Gods (Starz 2017–2021) and The Sandman (Netflix 2022– ), two highly watchable audiovisual series are adaptations of Neil Gaiman’s popular novel (2001) and of his earlier comic book series (1989–1996). They are both inspired by classical and Norse mythologies and reflect the evolution of culturally and socially important themes that occurred between the publication of their literary models and the airing of the television series. Curiously, the adaptation of the novel includes more Olympic gods but glosses over the influence of Herodotus. The Sandman, on the other hand, in its television version, and specifically, in its first season finale episode Calliope, under discussion here, is much less graphic in the scenes of sexual abuse leaving the more drastic images to the imagination of the viewers but at the same time achieving an even more expressive empathy toward the suffering victim and a severe condemnation of the committed outrage.